Specifics of Preparing the Geographic Basis for Historical Mapping - Datsenko, L. M.; Titova, S. V.; Dubnytska, M. V. (Ukrainian Geographical Journal, 2024)
Changes in physical-geographical minds are created not only by the influx of natural phenomena, but by the great world as a result of human activity. And the emphasis of scientists on obtaining old maps was until current research, but the preparation of geographical foundations for the creation of historical maps may not have been completed. This publication is devoted to the nutritional display of changes in the hydrological boundary of the river over historical periods. The research has established a method of analysis to verify the essential evidence of historical cartography, and a method of synthesis allows us to absorb the information obtained during the investigation to clarify the problem seen. Ignoring the power of reconstruction of the landscape for an hour period, which is mapped to result in the depiction of elements of a geographical basis and localization of thematic interest, while historical maps are often a single source of history personal spatial information.
Keywords: historical map; geographical basis; landscape reconstruction